SOCIO-PSYCHOLOGICAL FEATURES OF PERSONALITY FORMATION OF YOUNG LEADERS - Me'raj Salimovich Saidov (American Journals, 2024)
This article provides opinions on the role and importance of young leaders in the life of our country. What is a coping strategy, who introduced it to the science and how it is useful for young leaders is explained.
Keywords: Human resources, social psychology, emotion, personality, management psychology.